Spring Recipes - Mak, Gary.; Long, Josh.; Rubio, Daniel; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
With over 3 million users/developers, Spring Framework is the leading (3z(Bout of the box(3y (BJava framework. Spring addresses and offers simple solutions for most aspects of your Java/Java EE application development, and guides you to use industry best practices to design and implement your applications. The release of Spring Framework 3 has ushered in many improvements and new features. Spring Recipes: A Problem-Solution Approach, Second Edition continues upon the bestselling success of the previous edition but focuses on the latest Spring 3 features for building enterprise Java applications. This book provides elementary to advanced code recipes to account for the following, found in the new Spring 3: Spring fundamentals: Spring IoC container, Spring AOP/ AspectJ, and more Spring enterprise: Spring Java EE integration, Spring Integration, Spring Batch, jBPM with Spring, Spring Remoting, messaging, transactions, scaling using Terracotta and GridGrain, and more. Spring web: Spring MVC, Spring Web Flow 2, Spring Roo, other dynamic scripting, integration with popular Grails Framework (and Groovy), REST/web services, and more. This book guides you step by step through topics using complete and real-world code examples. Instead of abstract descriptions on complex concepts, you will find live examples in this book. When you start a new project, you can consider copying the code and configuration files from this book, and then modifying them for your needs. This can save you a great deal of work over creating a project from scratch!s
to Spring -- Advanced Spring IoC Container -- Spring AOP and AspectJ Support -- Scripting in Spring -- Spring Security -- Integrating Spring with Other Web Frameworks -- Spring Web Flow -- Spring @MVC -- Spring REST -- Spring and Flex -- Grails -- Spring Roo -- Spring Testing -- Spring Portlet MVC Framework -- Data Access -- Transaction Management in Spring -- EJB, Spring Remoting, and Web Services -- Spring in the Enterprise -- Messaging -- Spring Integration -- Spring Batch -- Spring on the Grid -- jBPM and Spring -- OSGi and Spring.
Keywords: Computer science; Computer Science; Programming Techniques